The influence of internal organizational mechanisms on gender mainstreaming effectiveness Morogoro region, Tanzania - Mwakiluma, Lusako; Matoka, Chacha (Advances in Social Sciences Research Journal, 2021)
pa name="_Toc79139055"/aa name="_Toc79138879"/aa name="_Toc79138703"/aThe paper sought to analyse the influence of the existing internal organizational mechanisms on gender mainstreaming effectiveness (GME). The study used cross sectional research design where a total sample of 368 respondents was drawn from population of 4481 by using systematic sampling from employees of the Morogoro Municipal Council, whereby questionnaire was the main tool used to collect data. The linear multiple and hierarchical regression models were used analyse data. The study found that a positive and significant influence of existing internal organizational mechanisms on gender mainstreaming effectiveness at Morogoro municipal council. The paper concludes that the GME was influenced greatly by the internal organizational mechanisms. Therefore, it is recommended that the Local Governmental Authorities to increase efforts of committing resources on the internal organizational mechanisms for gender mainstreaming effectiveness in the work place./p